Sistematização da assistência de enfermagem em Unidade de Terapia Intensiva Neonatal : desenvolvimento de um protótipo para ser utilizado em dispositivo móvel - Rezende, Laura Cristhiane Mendonça (2015)
Introduction: it is undeniable that the evolution of mobile computing devices, associated with the development of capacities for operation in wireless network, potencializes new ways to use them for nursing care provision, enabling to extend information systems up with the patient. Objectives: to developing an application for mobile device that allows data logging for systematization of nursing care in the Neonatal Intensive Care Unit (NICU) and implementing the prototype allowing to identify the nurses' perception about their use. Method: this is a methodological research of applied type, developed in the NICU of the Lauro Wanderley University Hospital, located in the city of João Pessoa, PB. The main technologies used for the development of software were the Ruby programming language, Ruby on Rails and JavaScript; Bootstrap framework; Ubuntu Linux production server, Nginx Webserver and PostgreSQL Database Management System. The software was developed in the period from May to September 2014 and used by nurses for thirty days, from 9th September to 9th October 2014. The study included five nurses who develop their activities in the NICU. To evaluating the application there was developed a semi-structured questionnaire and the results analyzed through the content thematic analysis of the method Bardin. There were obeyed guidelines inherent in the research protocol contained in Resolution No. 466/12, National Health Council (CNS). The project was approved and registered with the National Information System on Ethics in Research involving Human Subjects, with CAAE-25890914.5.0000.5183. Results: with respect to mobile technology used, in general, nurses do not present difficulties, because they have familiarity with this type of device. Those who experienced difficulties with the frequent use of the system, the obstacles were minimized. Overall, it is emphasized that the application includes features for SAE in NICU, but changes are suggested as the interface of screens and some terms of data collection and parameters available by the applicable. In the view of the study participants, the main contributions of software for mobile technology are: agility to develop and document the SAE, freedom of movement, evaluation of standardization of the newborn, time optimization in carrying out bureaucratic activities, ability to retrieve information and reducing the physical space occupied. Conclusion: therefore, a system for SAE in mobile technology allows flexibility in carrying out registration activities by the nurse, since the data collection can be performed at the bedside; in addition, offers numerous advantages to this professional work routine.